The World of the working children - Velez, Jose Mari. (Quezon City GMA Radio Television News and Public Affairs)
Poverty is the main reason why children work in streets, dump sites and other places. Most of them are engaged in scavenging, muro-ami fishing, household work, protitution, etc. Includes interviews with famous children who work as entertainers like Aiza Seguerra and Rose Ann Gonzales. Atty. Bautista explains the Child and Youth Welfare Code. The heads and officials of DSWD and the Institute for the Protection of Children talk about projects of their respective departments regarding child labor.
Host, Jose Mari Velez.
Keywords: Children -- Employment -- Philippines; Poor children -- Philippines